All‐Ceramic Flexible Piezoelectric Energy Harvester. (17th October 2022) - Liu, Yang; Ding, Libo; Dai, Le; Gao, Xuan; Wu, Hanzhou; Wang, Shuhao; Zhuang, Chenggang; Cai, Ling; Liu, Zhen; Liu, Lisha; Zhang, Ji; Wang, Yaojin
Abstract: With the rapid development of self‐powered electronics such as wearables, implantable devices, and sensor networks, there is an increasing demand for power sources that have a high power density and a long lifespan to keep the entire system operational. Flexible piezoelectric materials with the capability of mechanical‐to‐electrical energy conversion have attracted significant interest because of their immense potential for harvesting human biomechanical energy. Herein, 3 mol.% yttrium stabilized zirconia ribbon ceramic is selected as a unique substrate to manufacture a large‐scale and all‐ceramic flexible Pb(Zr0.52 Ti0.48 )O3 piezoelectric energy harvester via the cost‐effective one‐step process. The flexible piezoelectric energy harvester delivers excellent performance with an open‐circuit voltage of ~105 V and short‐circuit current of ~0.58 µA under mechanical strain equivalent to human movement. Moreover, the output voltage of a flexible piezoelectric energy harvester varies linearly with strain, allowing it a promising candidate as a self‐powered strain sensor. Of particular importance is that a large‐scale piezoelectric energy harvester (4 × 4 cm 2 ) can simultaneously light up eight commercial light emitting diodes without any external power source and circuit. This research provides an innovative approach to the fabrication of high‐performance and large‐scale flexible piezoelectric energy harvesters as well as self‐powered micromechanical devices. Abstract : A large‐scale and all‐ceramic flexible Pb(Zr0.52 Ti0.48 )O3 (PZT) piezoelectric energy harvester is developed with the unique 3 mol% yttrium stabilized zirconia ribbon ceramic as a flexible substrate, which delivers excellent output performance and mechanical stability under mechanical strain equivalent to human‐movement. This research provides an innovative approach to the fabrication of high‐performance and large‐scale flexible piezoelectric energy harvesters as well as self‐powered micromechanical devices.